Многоаспектность содержания права - Оборотов, Юрий Николаевич; Оборотов, Юрій Миколайович; Oborotov, Jurij (My University, 2012)
The content of law is usually understood as a system of legal norms. Transformations in modern society cause the crisis of social normativity in general and legal normativity in particular. Other aspects of the content of a law, such as values and information, are activating. Thus, the effectiveness of a modern law can be reached only by combining the normative and value aspects of the content of law.
Оборотов Ю. Н. Многоаспектность содержания права / Ю. Н. Оборотов // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 197-202.
Keywords: нормативное содержание права; кризис правовой нормативности; ценностное содержание права; ценностно-нормативное содержание права; нормативний зміст права; криза правової нормативності; ціннисний зміст права; ціннісно-нормативний зміст права; normative content of law; crisis of legal normativity; value content of law; value-normative content of law